Accessibility in a multiple transport mode urban park based on the "D-D" model: A case study in Park City, Chengdu. (March 2023) - Zhang, Ziyang; Ma, Guoqiang; Lin, Xiang; Dai, Haoyu
Abstract: Park City is a new concept for sustainable urban development. Urban Parks are the core of Park City, where park accessibility is the central index of park services. Previous studies have been conducted primarily from residents' perspective, based on the "O-D" (origin to destination) model to access the park accessibility. However, urban parks should be considered a place supporting the coexistence of tourists and residents. Moreover, tourists' movement patterns differ from those of residents, which are expressed as "no turning back" and traverse circular or nodal routes. Consequently, this paper proposes that the traditional "O-D" model be expanded to be consistent with the movement patterns of tourists. This paper employs Park City Chengdu as an exemplar and proposes a "D-D" (destination to destination) model to facilitate further park accessibility. The calculation process was based on a multiple transportation mode measure with multiple time thresholds, entrances, and exits, supported by Web API. The results reveal the key time nodes and park accessibility rankings for four transportation modes. In particular, the park accessibility presents a "dual-core, several sub-centers and cluster-types" circle structure. Furthermore, the park accessibility in Chengdu was generally balanced, except within 25 min, as well as walking and public transport. This paper provides new hypothetical perspectives and practical experiences for studying urban park accessibility, and novel ideas for parks' sites and distribution while serving as a model for cities worldwide for sustainable urban development. Highlights: "D-D" (destination to destination) model based on the travel behaviors of tourists to facilitate park accessibility Multiple transportation mode, time thresholds and entrances and exits, supported by Web API Determine the transportations' weights and time thresholds for spatial analysis by data itself New ideas for urban parks' sites and distributions "Park Stepping Stones" to form park networks based on "D-D" model results